The use of mobile devices with multi-tag technologies for an overall contextualized vineyard management - Cunha, Carlos R. (2010)
This paper describes a Viticulture Service-Oriented Framework (VSOF) which turns around context elements or tags that are placed in the field and which can be decoded by mobile devices such as mobile phones or PDAs. The tags are used to automatically associate a field location to the relevant database tables or records and also to access contextual information or services. By pointing a mobile device to a tag, the viticulturalist may download data such as climatic data or upload information such as disease and pest incidence in a simple way, without having to provide coordinates or any other references, and without having to return to a central office. This work is part of an effort to implement a large-scale distributed cooperative network in the Douro Demarcated Region in Northeast Portugal, a region in which the effort makes particular sense due to the extremely variable topography and mesoclimates. The possibility of exchanging contextualized information and accessing contextualized services in the field, using well-known devices such as cell phones, may contribute to increase the rate of adoption of information technology in viticulture, and contribute to more efficient and closer-to-the-crops practices.